ICD-10-Coding of Medically Unexplained Physical Symptoms and Somatoform Disorders—A Survey With German GPs - Pohontsch, Nadine J.; Zimmermann, Thomas; Lehmann, Marco; Rustige, Lisa; Kurz, Katinka; Löwe, Bernd; Scherer, Martin (Frontiers in Medicine, 2021)
Background: General practitioners (GPs) are reluctant to use codes that correspond to somatization syndromes. Aim: To quantify GPs' views on coding of medically unexplained physical symptoms (MUPS), somatoform disorders, and associated factors. Design and Setting: Survey with German GPs. Methods: We developed six survey items [response options “does not apply at all (1)”—“does fully apply (6)”], invited a random sample of 12.004 GPs to participate in the self-administered cross-sectional survey and analysed data using descriptive statistics and logistic regression analyses. Results: Response rate was 15.2% with N = 1,731 valid responses (54.3% female). Participants considered themselves familiar with ICD-10 criteria for somatoform disorders (M = 4.52; SD =.036) and considered adequate coding as essential prerequisite for treatment (M = 5.02; SD = 1.21). All other item means were close to the scale mean: preference for symptom or functional codes (M = 3.40; SD = 1.21), consideration of the possibility of stigmatisation (M = 3.30; SD = 1.35) and other disadvantages (M = 3.28; SD = 1.30) and coding only if psychotherapy is intended (M = 3.39; SD = 1.46). Exposure, guideline knowledge, and experience were most strongly associated with GPs' self-reported coding behaviour. Conclusions: Subjective exposure, guideline knowledge, and experience as a GP, but no sociodemographic variable being associated with GPs' subjective coding behaviour could indicate that GPs offer a relatively homogeneous approach to coding and handling of MUPS and somatoform disorders. Strengthening guideline knowledge and implementation, and practise with simulated patients could increase the subjective competence to cope with the challenge that patients with MUPS and somatoform disorders present.